Costa Rica a traveler's literary companion - Ras, Barbara (Whereabouts Press, 1994)
Contributors: Alfredo Aguilar, Fabian Dobles, Carlos Luis Fallas, Jaoquin Gutierrez, Carmen Lyra, Yolanda Oreauno, Julieta Pinto, Carlos Salazar Herrera, Rima de Vallbona, and more.